Скрытые неосознаваемые барьеры как причина неудач в процессе овладевания иностранным языком - Woźniewicz, Władysław (Studia Rossica Posnaniensia, 2014)
The article explains the meaning of the following expressions from a cognitive and linguistic perspective: competence and its types, learning/mastering a foreign language, and a cultural and linguistic personality. In the following part, in accordance with J. Habermas’s concepts, the author describes the components of the expression daily communication and explains how he understands the construct: hidden, unconscious communication barriers. The largest part of the article deals with describing the criteria for classifying communication barriers and the characteristics of three types of such barriers: contextual barriers, personality barriers of the communicants, including the unconscious, and involuntary barriers in everyday communication in teaching.